A Study of Sustainable Waste Management Using Theory of Planned Behaviour in Traditional Agricultural Markets - Nurchayati; R Clario Dimassetya Jaya; Widayati, Tri (Jurnal Manajemen & Agribisnis, 2023)
The waste management of agricultural commodities in traditional markets need serious attention as they remain because agricultural commodities usually pollute the streets and public spaces. This had a detrimental impact on both public health and traditional market image. By using the perspective of the Theory of Planned Behavior (TPB), the study was conducted to empirically examine the effects of attitudes, subjective norms, and perceived behavioral control (PBC) on the intention and behavior of separating waste in traditional markets. The research was conducted in a quantitative design. The sampling technique used was simple random sampling. A total of 210 agricultural commodity traders in traditional markets in Semarang was taken as sample in this study. The data was analyzed by using Structural Equation Modeling (SEM) with SmartPLS software. The results showed that attitudes, subjective norms, and PBC had significant effects on increasing intention in separating waste, which in turn would imply increasing the behavior in separating waste. The findings also report the mediating role of intention in strengthening the TPB constructs on behavior. This study emphasized the importance of establishing sustainable waste management and the connection between the behavior of waste management and to the adoption of a circular economy to make a more strategic impact to society and economy. Keywords: theory of planned behavior, agribusiness, waste management, traditional markets